Student evaluation of teacher digitals skills at Granada University - Santiago Alonso-García; Juan José Victoria-Maldonado; Pablo José García-Sempere; Fernando Lara-Lara (Frontiers in Education, 2023)
The following study is a descriptive/correlational analysis of students’ perception of digital competence in teaching. It is based on the current needs of university students with regard to the digitization of teaching and learning processes. Knowing student satisfaction with teaching digital skills could be used to propose improvements in the quality of university education to the extent that it can channel the various socio-economic demands. The European Higher Education Area is not oblivious to this problem by creating a framework of ambitious objectives for member states where ICT and digital competence of teachers are a priority. The research is carried out at the University of Granada and takes as a reference the framework: Marco Común de Competencia Digital Docente. This Framework in the context of Spain is concerned with indicating which areas educators need to acquire a skill higher degree differentiating between the following levels of classification: basic, intermediate and advanced. A quantitative correlational study was carried out, and an online questionnaire/form was distributed to a random probability sample of 307 students at the University of Granada belonging to different faculties of education. According to the results obtained, the students unanimously share the opinion that, the lecturers at Granada University do not possess a sufficient level of experience or training to competently deliver course content in a purely digital format.